2015
DOI: 10.1145/2701428
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Graphene Nanoribbon and Carbon Nanotube Based Floating Gate Transistor for Nonvolatile Flash Memory

Abstract: Abstract-Floating gate transistor is the basic building block of nonvolatile flash memory, which is one of the most widely used memory gadgets in modern micro and nano electronic applications. Recently there has been a surge of interest to introduce a new generation of memory devices using graphene nanotechnology. In this paper we present a new floating gate transistor (FGT) design based on multilayer graphene nanoribbon (MLGNR) and carbon nanotube (CNT). In the proposed FGT a multilayer structure of graphene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The distribution of the value of β is shown in figure 4(B) with a median value of 2.85 and a standard deviation of 0.59. This value agrees with the operating voltage of other graphene-based devices [12,13]. We attribute the overestimation of β in the other (non-device) reports to depositing graphene on a metal instead of a dielectric, which in turn shifts the Fermi energy and lowers the barrier for tunneling.…”
Section: Field Enhancement Factor Extractionsupporting
confidence: 87%
See 1 more Smart Citation
“…The distribution of the value of β is shown in figure 4(B) with a median value of 2.85 and a standard deviation of 0.59. This value agrees with the operating voltage of other graphene-based devices [12,13]. We attribute the overestimation of β in the other (non-device) reports to depositing graphene on a metal instead of a dielectric, which in turn shifts the Fermi energy and lowers the barrier for tunneling.…”
Section: Field Enhancement Factor Extractionsupporting
confidence: 87%
“…However, Hong et al reported graphenebased FG memory structure with a write voltage of only 7 V [12]. Also, Hossain et al reported a write voltage of 12 V for a FG structure using CNTs as the FG and multilayer graphene as the channel [13]. Although the reported write voltage is lower than the current industry standard (∼20 V) [12], it is still much higher than the values predicted based on the β values previously mentioned.…”
Section: Introductionmentioning
confidence: 85%
“…In contrast, the C GD of the FPS-DMOSFET has additional capacitance factors originating from the FPS, active gate, and n-drift, as shown in Figure 5b [20]. Therefore, the total C GD of the FPS-DMOSFET can be expressed as follows:…”
Section: Fps-dmosfet Optimizationmentioning
confidence: 99%
“…Emerging material-based floating-gate transistors, such as organic semiconductors, 9−12 metal oxides, 13,14 carbon nanotubes, 15,16 perovskites, 17,18 and two-dimensional materials, 19−21 have been developed widely in recent years. Rather than using conventional silicon MOSFETs, the use of these materials as an active layer or a floating-gate provides new functionalities, including mechanically flexible properties, 22,23 synaptic behaviors, 24−27 and logic-in-memory operation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Emerging material-based floating-gate transistors, such as organic semiconductors, metal oxides, , carbon nanotubes, , perovskites, , and two-dimensional materials, have been developed widely in recent years. Rather than using conventional silicon MOSFETs, the use of these materials as an active layer or a floating-gate provides new functionalities, including mechanically flexible properties, , synaptic behaviors, and logic-in-memory operation. , With this viewpoint, a photo-activated floating-gate memory device was proposed. In these devices, photodetection and memory functions are combined in a single device, where the unnecessary signal delay can be alleviated, and the function of two different elements can be performed simultaneously so that the image recognition system can be miniaturized by reducing the metal wiring between the photodetector and the memory element.…”
Section: Introductionmentioning
confidence: 99%